Impact of Compliance with Food Safety Measures in Fish Processing Units - Gupta, Shiwangi; Kumar, Nalini Ranjan; Krishnan, M; Immanuel, Sheela (Fishery Technology, 2025)
Increasing consumer demand for greater food safety, particularly in developed countries has triggered the need for an integrated approach for ensuring food safety in the entire food production chain viz., from farm to fork. This study estimates the cost of compliance with food safety measures in fish processing plants. The study is based on primary data collected from 14 fish processors cum exporters in West Bengal in the year 2011. West Bengal is one of the largest seafood exporters and contributes about 9% to the total seafood export from India. The study shows that status of compliance with food safety measures in Indian fish processing plants is satisfactory. Though the cost of compliance with food safety is high, it is beneficial to processor/ exporter in better price realization and acceptance of the products in international markets. The compliance with food safety measures can be further enhanced by easy and cheap availability of credit to processors and capacity building of all stakeholders in fish supply chain for their better adoption at lower level of supply chain to ensure safe raw material for the processing industries.